Country-level interventions for the prevention and management of hypertension through the modification of social determinants of health: a systematic review protocol - Arabi Basharic, Fateme (Syst Rev, 2020)
BACKGROUND: Hypertension is one of the public health challenges. Various risk factors are associated with hypertension, including social demographics, geographical location, health behaviours, and social stress. Interventions in the social determinants of health can improve hypertension and health promotion. Accordingly, different sectors such as agriculture, housing, education, and transportation should cooperate. This systematic review examines policies as a set of activities and actions/interventions aimed at the modification of the social determinants of health to prevent hypertension. METHODS: A systematic search will be conducted in Medline (via Ovid), PubMed, EMBASE, Cochrane Library, ProQuest Dissertations & Theses, and scientific Persian databases including SID and Magiran. There will be no time restriction. The quality of selected studies will be assessed using an appropriate Joanna Briggs Institute (JBI) Critical Appraisal Checklists according to the type of studies. Two independent researchers will carry out screening and quality assessment. Disagreement between two researchers will be resolved by a third party. DISCUSSION: Recommendations will be made for policymakers in order to make better evidence-based decisions about the prevention and management of hypertension with regard to the social determinants of health. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42020152298